3D Modelling and Performance Analysis of Dual Material Tri-Gate Tunnel Field Effect Transistor. Issue 2 (4th March 2019) - Saha, Priyanka; Sarkhel, Saheli; Sarkar, Subir Kumar
ABSTRACT: This work presents a detailed three-dimensional analytical modelling and simulation study of a dual material tri-gate (DM TG) tunnelling field effect transistor (TFET) obtained by intermixing the concepts of tri-gate architecture and dual material gate in the widely popular TFET structure. The proposed model aims to tune the tunnelling barrier in the channel region at the source channel junction so that the band-to-band tunnelling of carriers occurs at a significant rate and reaches the drain region efficiently under the influence of enhanced gate control over the channel region, thereby increasing the device ON current. An overall performance comparison of the proposed DM TG-TFET with that of its single-metal tri-gate (SM TG) TFET counterpart has been depicted to establish the effectiveness of the proposed DM TG-TFET structure. Analytical results have been compared with SILVACO ATLAS device simulator results to validate our present model.